Bismuth and chromium co-doped strontium titanates and their photocatalytic properties under visible light irradiation1. Issue 39 (21st October 2015) - Lv, Meilin; Xie, Yinghao; Wang, Yawei; Sun, Xiaoqin; Wu, Fangfang; Chen, Hongmei; Wang, Shuwei; Shen, Cai; Chen, Zuofeng; Ni, Shuang; Liu, Gang; Xu, Xiaoxiang
<x xml:space="preserve">Abstract</x> Bi/Cr were co-doped into SrTiO3via two synthetic routes. Unlike Cr, Bi does not significantly contribute to the electronic structure near Fermi level.